Kinerja Pegawai terhadap Pelayanan Satu Pintu di Kabupaten Enrekang - Rahmayani, Rahmayani; Hariyanti Hamid; Andi Uceng; Lukman, Lukman (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study is motivated by the importance of the role of employee performance in supporting the success of public services, especially one-stop integrated services in Enrekang Regency. The problems found include inconsistencies in information, lack of clarity in service procedures, and public dissatisfaction with services. The purpose of this study is to determine the extent to which employee performance affects the quality of one-stop services and to identify the factors that influence it. This study uses a quantitative descriptive approach with data collection techniques in the form of observation, questionnaires, and literature studies. The research sample was 89 respondents from a total population of 778 people who had been served by the Investment and One-Stop Integrated Services Office of Enrekang Regency. Data analysis was carried out using reliability tests and simple linear regression through the assistance of SPSS version 26. The results of the study showed that employee performance had a significant effect on service quality, with 73% of respondents assessing employee performance in the good category, and 72.8% assessing the service also in the good category. Factors that influence performance such as expertise, knowledge, work design, and work motivation have a contribution of 70.3%. This study concludes that improving employee performance is very important in supporting the success of the one-stop service system. Continuous coaching, training and improvement of information systems are needed to increase public satisfaction with public services.